Development of a method for the screening and quantification of methamphetamine, and its major metabolite amphetamine, in hair using liquid chromatography-tandem mass spectrometry - Johnston, Jenna (Division of Forensic Medicine and Toxicology, 2015)
Hair has, over recent years, become widely recognised as an alternate or complementary matrix to blood and urine for drug analysis. Hair analysis offers a wider detection window after drug exposure than blood or urine testing and can provide a long-term history of an individual’s drug use. There are several practical applications of hair analysis for drugs including workplace drug testing, doping control, driving licence re-granting, drug-related deaths and drug-facilitated crimes. As a result hair analysis is currently being performed within various toxicological fields in laboratories around the world. However, before the start of this study no hair analysis for drugs was being performed in South Africa. Therefore, the main aim of this study, as stated in Chapter 1, was to develop a method for the detection and quantification of drugs of abuse, specifically methamphetamine and amphetamine, in hair using High Performance Liquid Chromatography coupled to Mass Spectrometry.